Bogotá and Medellín - Future mobility for Socially Inclusive Cities. - Hoelscher, Martin (Lit, 2020)
This article focusses on strategies that use infrastructure to promote it. Bogotá and Medellín, the two biggest Columbian cities, implemented internationally recognized best practices in creating innovative mobility systems as initial steps towards integrated urban development.
Keywords: Integrierte Stadtentwicklung; Nachhaltige Mobilität; ÖPNV; Inklusion; Verkehrsinfrastruktur; Multimodalität; Verkehrspolitik; Best Practice